Hubungan Pengetahuan dan Sikap dengan Perilaku Merokok Santriwan di Pondok Pesantren Al-Jihad Surabaya - Dwi Handayani (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2019)
Smoking is one of the health risk behaviors that increasingly threatens young and even teenagers. Not only in public schools, but also the increasing number of Islamic boarding schools. Even in some Islamic boarding school activities, in addition to serving food, the boarding school also provides treats for cigarettes. This is a challenge that is still difficult to resolve, because the age of smokers is getting younger. This study aims to find out the relationship between knowledge and attitude with smoking behavior of students in Surabaya Al Jihad Islamic Boarding School. Method: This study was an analytic observational study with crossectional design. The population of this research is all students who live in Al Jihad Islamic Boarding School Surabaya. The study sample was 97 respondents who were selected by random sampling. Data collection is done by interviewing using a questionnaire. Data were analyzed using the chi square test. This study shows that there is no significant relationship between knowledge (p = 0.885) and santriwan smoking behavior. But there is a significant relationship between attitudes and santriwan smoking behavior (p = 0.025). Strengthening the knowledge and attitudes of santrians regarding smoking is important, because this can affect the smoking behavior of santri in Islamic boarding schools. It is expected that the leaders and managers of Islamic Boarding Schools are committed to implementing a non-smoking area by providing warning bans on smoking around Islamic boarding schools